If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1p + 3 + 2.4 + -2p = 0 Reorder the terms: 3 + 2.4 + -1p + -2p = 0 Combine like terms: 3 + 2.4 = 5.4 5.4 + -1p + -2p = 0 Combine like terms: -1p + -2p = -3p 5.4 + -3p = 0 Solving 5.4 + -3p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5.4' to each side of the equation. 5.4 + -5.4 + -3p = 0 + -5.4 Combine like terms: 5.4 + -5.4 = 0.0 0.0 + -3p = 0 + -5.4 -3p = 0 + -5.4 Combine like terms: 0 + -5.4 = -5.4 -3p = -5.4 Divide each side by '-3'. p = 1.8 Simplifying p = 1.8
| 3x+1/2+2x=61/2 | | -7d-9=-30 | | 9x^2+3=-8x | | -11=r-5+r | | 2(9+4x)=106 | | 8x+12=92 | | 10x+4.5+x-8= | | c(m)=0.5m+45 | | 5x+2=23 | | 10m=14+3m | | 5(y+1)=3y+7 | | 4x-2/7=306/7 | | 1.5x+1.5c=30 | | (5t^2-t-7)*(6t^2+5t-1)= | | 12*5/3+x=45 | | 68/x+96-23=90 | | 4=x-3 | | 315/9+x-42=72 | | -11y=-88 | | x+6=70/11 | | 15*4+x=115 | | x*5/2+25=100 | | 3x-3c=30 | | x/-5=-6 | | 3(c+1)=2c-3 | | 482/2-32+x=410 | | (5x-3)(x^2-6x+6)= | | 2(7v+9)-8(3v+3)= | | -16=x+5 | | 22*x+40-110=150 | | 3x+5-x=5+x+1 | | .25X^2+2.6X-116.4=0 |